Influence of the baroclinic effects on the structures of planetary boundary layer of the atmosphere - Quang, Le Dinh (Vietnam Journal of Mechanics, 1982)
The influence of the baroclinic effects on the fundamental characters of the atmospheric boundary layer atmosphere is studied. The obvious difference between the structures of boundary layer of both baroclinic and barotropic cases is presented. Especially the baroclinic effect on the low latitude may not be neglected.